Addressing America’s Current and Future Educational Challenges: The Renaissance Group President’s Perspective - Counts, John (Educational (Re)naissance, 2012)
<!-- @font-face { font-family: "Cambria"; }p.MsoNormal, li.MsoNormal, div.MsoNormal { margin: 0in 0in 0.0001pt; font-size: 12pt; font-family: "Times New Roman"; }div.Section1 { page: Section1; } --> Experience informs us that, after parents and guardians, educators have the greatest level of influence on children of all ages. These are the educators we prepare on our university campuses every semester, year after year, for whom the act of teaching is much more than a monthly paycheck, but is rather a very special calling. <!-- @font-face { font-family: "Cambria"; }p.MsoNormal, li.MsoNormal, div.MsoNormal { margin: 0in 0in 0.0001pt; font-size: 12pt; font-family: "Times New Roman"; }div.Section1 { page: Section1; } --> Parents, whose children are taught by the teachers and administrators our universities prepare, typically praise their local schools, teachers, administrators and support personnel. However, when we move beyond these familial educational settings, the general level of criticism directed toward our public schools and schools of education has never been higher.